Cross-border diversification in bank asset portfolios - Claudia M. Buch; John C. Driscoll; Charlotte Ostergaard (European Central Bank (ECB), 2005)
Taking the mean-variance portfolio model as a benchmark, we compute the optimally diversified portfolio for banks located in France, Germany, the U.K., and the U.S. under different assumptions about currency hedging. We compare these optimal portfolios to the actual cross-border assets of banks from 1995-1999 and try to explain the deviations. We find that banks over-invest domestically to a considerable extent and that cross-border diversification entails considerable gain. Banks underweight countries which are culturally less similar or have capital controls in place. Capital controls have a strong impact on the degree of underinvestment whereas less political risk increases the degree of over-investment.
Keywords: G21; G11; E44; F40; 330; International banking; international integration; portfolio diversification; Portfolio-Management; Portfolio-Investition; Internationale Bank; Hedging; Währungsrisiko; Frankreich; Deutschland; Großbritannien; USA